Speaking Assistance Through Song Material for Class X Students of Islamic Boarding School Mambaul Ihsan - Widodo, Arif; Ainak, Roihanatul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
Carrying out Community Service Activities is one of the tridarma of higher education in helping solve problems, especially aspects of Education. This activity aims to: (1) provide assistance to students regarding mastery of speaking skills using the song method, (2) provide training on Arabic songs, (3) assistance in learning to speak with songs. The method used is a participatory approach that starts with pre-material, material and evaluation. This activity was carried out in November 2022 involving 16 students. The results of the activity showed that 1) students had direct experience singing Arabic songs; 2) students find it helpful in speaking Arabic; 3) as many as 16 students have been able to communicate limitedly using Arabic through songs and the material presented through songs has appeal and can motivate children.